INTERNAL EMPLOYEE QUALIFICATION AFFECT ADAPTABILITY TO OPEN OFFICE LED TO WORKPLACE SATISFACTION - Kotamena, Fredson; Bing Andika, Carter; Senjaya, Pierre (Dinasti Publisher, 2020)
This study aims to understand the internal employee qualification and separated all external factors like acoustic, thermal comfort, layout, air quality, and lighting surrounding the employee when adapting to open office. The questionnaire distributed on-line purposive given to those working in an open office environment. Some snowballing effect is happening, and we get 138 respondents. Structured equation modeling used for the hypothesis test. Results show that external factors are more influential in terms of adaptation to the concept of open office compared to internal conditions such as age, gender, length of career, and length of service. Only the level of position had a strong influence on the adaptation to open office internally. Company management needs to pay attention to the design layout, airflow, and lighting to add an atmosphere that matches the current millennial conditions and liking. Considering position level have a significant impact on internal employee qualification, then someone in the top leadership position would be able to influence junior level of adaptation to open office.